2009
DOI: 10.1136/emj.2008.059345
|View full text |Cite
|
Sign up to set email alerts
|

Emergency intubation: a prospective multicentre descriptive audit in an Australian helicopter emergency medical service

Abstract: Well-trained doctor paramedic teams, utilising standardised operating procedures, can safely perform rapid sequence induction and ETI in the prehospital and emergency environment. However, prehospital doctors are not always able to anticipate a difficult airway. The complication rate was similar to that in hospital emergency departments and to that of other physician-led HEMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
3
29
0
3
Order By: Relevance
“…Field intubation procedures are associated with more difficulty and complications than in-hospital procedures because of a wide range of factors. [144][145][146][147][148][149][150] Further, prehospital intubation is not always available and the ability to perform this procedure safely varies among prehospital EMS personnel, with physicians having the highest success rates. [144][145][146][147][148][149][150][151] Prioritizing advanced airway management and spinal immobilization may also delay release and rescue procedures as well as make the trauma examination more difficult, both at the scene, during transport, and at admittance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Field intubation procedures are associated with more difficulty and complications than in-hospital procedures because of a wide range of factors. [144][145][146][147][148][149][150] Further, prehospital intubation is not always available and the ability to perform this procedure safely varies among prehospital EMS personnel, with physicians having the highest success rates. [144][145][146][147][148][149][150][151] Prioritizing advanced airway management and spinal immobilization may also delay release and rescue procedures as well as make the trauma examination more difficult, both at the scene, during transport, and at admittance.…”
mentioning
confidence: 99%
“…[144][145][146][147][148][149][150] Further, prehospital intubation is not always available and the ability to perform this procedure safely varies among prehospital EMS personnel, with physicians having the highest success rates. [144][145][146][147][148][149][150][151] Prioritizing advanced airway management and spinal immobilization may also delay release and rescue procedures as well as make the trauma examination more difficult, both at the scene, during transport, and at admittance. 13,96,152 Delayed definitive care can be detrimental for patients with non-neurological critical injuries, and importantly, also lead to neurological progression, because spinal injuries are often neurologically unstable, but biomechanically stable in the acute phase.…”
mentioning
confidence: 99%
“…With this system, the mortality could be reduced, and if mandatory procedures were required (eg, intubation), there was a substantial time reduction as substantiated by findings from other countries [7,26]. Iirola et al [29] reviewed the importance of physician-staffed helicopter emergency services and found a more extensive treatment by the physician-staffed services without increasing scene time.…”
Section: Discussionmentioning
confidence: 88%
“…However, a study of one type of videolaryngoscope known for high rates of in-hospital success showed a success rate of only 47% (compared with 99% using direct laryngoscopy) when used by experienced practitioners during PHEA [46]. Pre-hospital tracheal intubation success rates by PHEM teams compare favourably with in-hospital emergency department rates [47,48]. Most systems train teams to provide a surgical airway in the event of a 'can't intubate, can't oxygenate' scenario, with the incidence of surgical airway provision in the order of 1% of patients requiring pre-hospital advanced airway support [49].…”
Section: Specialty-specific Phem Themesmentioning
confidence: 99%